Drought over Europe in recent years - Bordi I.; Sutera A. (Drought management: scientific and technological innovations, 2008)
In drought management, the transition from crisis to risk management defies a straightforward solution mainly because very few works have been done to address the risks associated with a drought, and to identify the factors that influence the vulnerability of a region. To promote this process and in view of the recent scientific debate on climate change, an important first step is the analysis of drought variability in the last years. Motivated by this issue, an analysis of drought in Europe using reanalysis data is provided, updated to December 2007. Because precipitation is an important water resource supply component and, thus, a critical parameter for drought risk assessment, we apply the most popular drought index based on precipitation to evaluate dry/wet conditions in the area, i.e. the Standardized Precipitation Index (SPI). Particular attention has been devoted to the variability of the linear trend unveiled in the SPI time series.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)